Early versus late initiation of renal replacement therapy in patients with acute kidney injury: a meta-analysis of randomised clinical trials (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY The optimal timing of renal replacement therapy (RRT) initiation in acute kidney injury (AKI) remains a matter of debate. A systematic review and meta-analysis of randomised controlled trials (RCTs) was conducted to better estimate the effects of early initiation of RRT compared with late initiation of RRT among patients with AKI and in patients at risk for AKI. METHODS A Medline literature research was conducted in PubMed for RCTs in adult patients with AKI that compared different RRT initiation strategies (early vs late). The meta-analysis outcomes were in-hospital or ≤60 day mortality, and renal recovery. RESULTS Nine trials meeting inclusion criteria and four trials investigating preventive dialysis in patients at risk for AKI were identified. Early initiation of RRT was not associated with reduced in-hospital or 60-day mortality: risk ratio (RR) 0.91, 95% confidence interval (CI) 0.72–1.16, p = 0.46, I2 = 49%). When only the four trials that offered RRT within 6 to 12 hours of eligibility were included in the analysis, the results were similar (RR 0.93, 95% CI 0.82–1.06) without significant heterogeneity. The percentage of patients among survivors who recovered enough kidney function to be off dialysis was similar with early compared with late RRT: RR 1.02, 95% CI 0.99–1.06, p = 0.16. Early initiation of RRT was associated with higher incidence of catheter-related infections: RR 1.82, 95% CI 1.03–3.21, p = 0.04. No survival benefit was identified in patients undergoing preventive dialysis: RR 0.85 (95% CI 0.52–1.41, p = 0.54). CONCLUSIONS Early RRT in patients with AKI (or at risk for AKI) does not appear to provide a significant reduction in mortality rates compared with late RRT. The data did not suggest any apparent impact on renal recovery with early dialysis. Meta-analysis registration number CRD42016045603, PROSPERO registry